Uncertainty in Solar Thermal Systems Simulations - Kalogirou, Soteris A. (My University, 2008)
Usually solar systems are modeled with programs, like TRNSYS, using a typical meteorological year data and a constant consumption profile. This is the most practical method as all systems modeled are simulated with the same weather conditions and the same load demand profile, thus it is easier to compare systems of different configurations. In this paper the effect of introducing uncertainty or noise in the weather data and load pattern is examined. As it is proved the annual performance of the system is not very much different compared to the normal non-noisy model whereas the daily and hourly performance shows some considerable variations. It is believed that the present method gives more reliable results to the long-term performance evaluation of the systems and should be followed once the optimum system is obtained as it produces more reliable results. This is more important in case where guaranteed solar results schemes are followed where possible mistakes could result in significant financial penalties
Keywords: Modeling of solar systems; Simulation, uncertainty; Long-term performance